APARI Education and Strengthening the Competency of Insurance Brokerage Human Resources in the Era of Change - Angky Sasongko; Sitti Rakhman (Journal of Social Research, 2026)
The contemporary insurance industry is undergoing significant transformation, marked by increasing risk complexity, accelerated digitalization, and deeper integration of global financial markets. These developments have intensified the demand for strengthening the competencies of insurance brokerage human resources through professional education that is not only adaptive but also context-sensitive. In practice, insurance brokers are no longer expected to function merely as transactional intermediaries; instead, they are increasingly required to assume the role of strategic risk advisors equipped with analytical capability, professional integrity, and a sound understanding of modern risk dynamics. (OECD, 2019; Susskind & Susskind, 2015) Within the Indonesian context, professional education and training programs organized by the Indonesian Insurance and Reinsurance Brokers Association (APARI) play a crucial role in shaping individual competencies to meet these evolving demands. This article seeks to reflect conceptually on the role of APARI professional education in strengthening the competencies of insurance brokerage human resources amid an era of rapid industry change, encompassing digital transformation, governance requirements, risk complexity, and global competition. This study employs a systematic literature review combined with conceptual analysis of professional education curricula, competency frameworks aligned with the Indonesian National Work Competency Standards (SKKNI) and the Indonesian National Qualifications Framework (KKNI), regulatory provisions issued by the Financial Services Authority (OJK), and selected international best practices in insurance professional education. The findings suggest that graduate quality does not emerge from a single determinant; rather, it develops through a dynamic interaction between curriculum relevance, learning approaches, and their practical alignment with industry realities. Beyond technical expertise, the development of soft competencies—such as professional communication, ethics, and adaptability—appears to be critical in shaping broker professionalism in the modern era. This article concludes that APARI professional education plays a strategic role in enhancing the competitiveness and long-term sustainability of Indonesia's insurance brokerage profession.